Analisis Manajemen Strategi Pelayanan Perizinan pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Tanjung Balai - Afriani Afriani; Purnama Ramadani Silalahi; Atika Atika (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Licensing services are an important component in supporting the investment climate and ease of doing business in the region. This study aims to analyze the management of licensing service strategies at the Tanjungbalai City Investment and One-Stop Integrated Services Office (DPMPTSP). The analysis includes organizational strategies, program strategies, resource support strategies, and supporting and inhibiting service factors. The research method uses a qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study show that DPMPTSP has implemented digital-based services through the Online Single Submission (OSS) system, Building Management Information System (SIMBG), and Sicantik Cloud. The implementation is supported by the strengthening of Standard Operating Procedures (SOPs) and improving the quality of human resources. However, the implementation still faces obstacles in the form of network disruptions, limited technology infrastructure, and a limited number of service officers. Therefore, optimizing digital-based licensing services requires stable infrastructure support, increased apparatus capacity, and continuous coordination between stakeholders. This research contribution emphasizes the importance of an adaptive, integrative, and quality-oriented licensing service management strategy to support sustainable regional economic development.